Motion Graphic Dalam Mendukung Penyampaian Pesan Game Show Edukasi “Clash Of Champions” - Sanjaya, William (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
Motion graphics have functions that allow messages to be delivered efficiently and attractively to the audience. "Clash of Champions" is an educational game show that applies motion graphics throughout the video so that the message can be delivered well. This study was conducted to discuss the application of the function of motion graphics in supporting message delivery in "Clash of Champions". The method used is qualitative with a purposive sampling approach. The theory used is the motion graphic theory proposed by Austin Shaw. From the research that has been done, it is concluded that there are motion graphics in the form of infographics, kinetic typography, and characters. Infographics describe the profiles of participants, situations, games, and results throughout the video. Kinetic typography gives a "technological" feel to the text display. Character-based motion graphics are used to show the figure of the tutor who delivers important information at the event. Thus, the application of motion graphics in "Clash of Champions" can provide information efficiently so that the videos displayed are informative, persuasive, and inspiring for the audience.